2015
DOI: 10.1186/s12891-015-0645-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with magnetic resonance imaging defined patellar tendinopathy in community-based middle-aged women: a prospective cohort study

Abstract: BackgroundPatellar tendinopathy identified by imaging modalities has been reported in asymptomatic athletes and associated with tendon-related symptoms. However there is little data in community-based populations. The aim of this cohort study was to examine the prevalence of magnetic resonance imaging (MRI) defined patellar tendinopathy, the factors associated with this condition, and whether it was associated with knee pain in community-based middle-aged women.MethodsOne hundred seventy six women, aged 40–67 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Multiple studies focused on risk factors of PT [9, 34, 37, 41]. However, no previous study identified evidence-based prognostic outcome factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies focused on risk factors of PT [9, 34, 37, 41]. However, no previous study identified evidence-based prognostic outcome factors.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced muscular flexibility has been determined as an intrinsic risk factor for PT in athletes [2, 41]. Additionally, PT is commonly observed in older and obese patients as well as in subjects exhibiting an increased vastus medialis muscle size [9, 33, 34]. Some investigators believe that the inferior pole of the patella has a propensity to impinge upon the deep surface of the proximal patellar tendon during knee flexion [14, 21, 33].…”
Section: Introductionmentioning
confidence: 99%
“…Patellar tendinopathy (PT) is a common pathology in athletes performing repetitive jumping sports such as basketball and volleyball [ 1 – 4 ]. Recent studies suggest PT to emerge as an overuse of the knee joint extension mechanism and prolonged repetitive mechanical stress [ 4 – 15 ]. Athletes typically complain about anterior knee pain, leading to a reduction of exercise load and decline in the level of competition [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is good evidence that repetitive mechanical stress plays a key role in the development of tendinopathy. The prevalence of patellar tendinopathy (jumper's knee) is greater in individuals with high levels of physical activity . For volleyball players, who have an unusually high incidence of patellar tendinopathy, the likelihood of developing jumper's knee increases significantly with increased training volume .…”
mentioning
confidence: 99%